Poverty problems for a patriot parliament - Dunne, John Patrick (Statistical and Social Inquiry Society of Ireland, 1923)
When planning the submission of certain suggestions as to Irish social legislation, designed to combat the evil of poverty, I conjectured that when the time arrived for doing so the battle flags would have been furled and tri-colours, whether of red, white and blue, or orange, green and white, would have ceased to serve as oriflammes to the people of Ireland. However, although the Irish Senate has not yet entered on its legislative stride I still hope that an Irish Constitution will soon be evolved, within which every element of class, creed and thought will find expression for their respective views, and Christ's poor especially some eloquent and energetic advocates.
Read April 28, 1922
Keywords: Irish Free State; Legislation reform; 314.15